Risk factors for hospital-acquired infection during the SARS-CoV-2 pandemic. (March 2023) - Kwon, J.H.; Nickel, K.B.; Reske, K.A.; Stwalley, D.; Dubberke, E.R.; Lyons, P.G.; Michelson, A.; McMullen, K.; Sahrmann, J.M.; Gandra, S.; Olsen, M.A.; Burnham, J.P.
Summary: Objective: To evaluate risk factors for hospital-acquired infection (HAI) in patients during the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic, including historical and concurrent cohorts. Design: Retrospective cohort. Setting: Three Missouri hospitals, data from 1 st January 2017 to 30 th September 2020. Participants: Patients aged ≥18 years and admitted for ≥48 h. Methods: Univariate and multi-variate Cox proportional hazards models incorporating the competing risk of death were used to determine risk factors for HAI. A - priori sensitivity analyses were performed to assess the robustness of the urine-, blood- and respiratory-culture-based HAI definition. Results: The cohort included 254, 792 admissions, with 7147 (2.8%) HAIs (1661 blood, 3407 urine, 2626 respiratory). Patients with SARS-CoV-2 had increased risk of HAI (adjusted hazards ratio 1.65, 95% confidence interval 1.38–1.96), and SARS-CoV-2 infection was one of the strongest risk factors for development of HAI. Other risk factors for HAI included certain admitting services, chronic comorbidities, intensive care unit stay during index admission, extremes of body mass index, hospital, and selected medications. Factors associated with lower risk of HAI included year of admission (declined over the course of the study), admitting service and medications. Risk factors for HAI were similar in sensitivity analyses restricted to patients with diagnostic codes for pneumonia/upper respiratory infection and urinary tract infection. Conclusions: SARS-CoV-2 was associated with significantly increased risk of HAI.